Pre-Hispanic exploitation of Rhea americana (ñandú - greater Rhea) by hunter-gatherer groups from the southern end of the La Plata River basin (Argentina and Uruguay) - Acosta, Alejandro; Loponte, Daniel; Gascue, Andrés; Bortolotto, Noelia (Arqueología, 2023)
In this paper, we analyze the exploitation of Rhea americana (greater Rea or ñandú) by hunter-gatherers that occupied the southernmost end of the La Plata River basin during the late Holocene. To this end, we present data on the faunal assemblages –including bones and eggshell fragments– recovered at 21 archaeological sites. Based on the taxonomic abundance, patterns of anatomical representation, and bone surface modifications, we evaluate the strategies and tactics related to their exploitation. These aspects are compared and discussed based on historical sources and the record of R. americana in other sites of the region and adjacent areas. The results show that, except for a single site (Cañada Saldaña), this species is poorly represented, with a predominance of hind limbs. This evidence suggests that its exploitation was centered on obtaining tendons, marrow, and, to a lesser extent, bones for artifact manufacture. The scarce archaeological representation of this species, both in the analyzed sites and in nearby regions, could be due to high capture costs. In this regard, various historical sources indicate that Rhea would not have been an easy prey to capture. It is possible that the European conquest, especially with the adoption of horses and the growing trade of Rhea feathers, led to a modification in the exploitation of this bird since it began to be a more frequent prey than in pre-Columbian times.